Regulatory T Cells are Baby′s Best Friends. (7th January 2013) - Teles, Ana; Zenclussen, Ana Claudia; Schumacher, Anne
<x xml:space="preserve">Abstract</x> Regulatory T cells (Treg) are one of the most and best studied immune cell population during human and murine pregnancy, and there is a general consent about their expansion during pregnancy. However, the identification of new and more reliable Treg markers during the last years resulted in some controversies about the kinetics of various Treg subsets at different pregnancy stages. No doubt exists regarding the importance of Treg for a normal pregnancy as pregnancy complications like spontaneous abortion and preeclampsia could be associated with a reduced Treg number and activity. In future, more attention should be paid to bring established data from the bench to the bedside to force the development of adequate therapies for treatment of pregnancy complications. In this article, we summarize previous and recent data on several aspects of Treg biology during human and murine pregnancy.